Stable surface oxygen on nanostructured silver for efficient CO2 electroreduction - Jee, Michael Shincheon; Kim, Haeri; Jeon, Hyo Sang; Chae, Keun Hwa; Cho, Jinhan; Min, Byoung Koun; Hwang, Yun Jeong (ELSEVIER SCIENCE BV, 2017)
We investigated properties involved in the enhancement in electrocatalytic carbon dioxide (CO2) reduction to carbon monoxide (CO) in electrochemically treated Ag surfaces with surface sensitive analysis methods such as Auger spectroscopy, atomic force microscopy (AFM) coupled with Kelvin probe force microscopy (KPFM) techniques, and near edge X-ray absorption fine structure (NEXAFS) spectroscopy. The absence of Ag M(4,5)VVAuger signals for the electrochemically treated Ag indicate the presence of localized surface oxygen (O) which survives on the best performing Ag electrocatalysts even in the reductive environment of the CO2 reduction reaction. Higher work functions were located at the nanostructure boundaries observed by KPFM/AFM implying the higher surface O concentrations in these regions. Furthermore, NEXAFS measured the selective prominence of pi* states over sigma* in the active Ag surfaces which suggests stronger interaction with intermediates of CO2 reduction while minimizing the OH interaction contributing to increase CO2 reduction activity and selectivity. These results provide direction in engineering surfaces for efficient electrochemical CO2 conversion. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CARBON-DIOXIDE REDUCTION; RENEWABLE ENERGY; ELECTRODES; NANOPARTICLES; CATALYSTS; AG; ELECTROCATALYST; MONOLAYERS; CONVERSION; STABILITY